Komunikasi Rekonsiliasi melalui Tradisi Mangan Murum di Bener Meriah - Arief Fadhillah; Rusli Yusuf; Ishak Hasan; Masrizal; Ella Fitriana (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines reconciliation communication through the Mangan Murum tradition in Bener Meriah Regency as a sociocultural space for rebuilding relationships among post-conflict multiethnic communities, particularly the Acehnese, Gayo, and Javanese. It analyzes how reconciliation communication is constructed through local cultural practices involving multiple social actors across the stages of initiation, dialogue, and collective ritual enactment. Using a qualitative approach with critical autoethnography, the researcher actively participated in the reconciliation process from stakeholder engagement to the implementation of the Mangan Murum ritual on August 10, 2025. Data were collected through participant observation, in-depth interviews, documentation, and reflective field notes. The findings show that reconciliation is gradually constructed through communication processes embedded in social interactions and cultural rituals rather than formal institutional mechanisms alone. The Mangan Murum tradition functions as a symbolic communicative space that restores trust, solidarity, and collective identity among communities affected by conflict. This study proposes the concept of Ritual Reconciliation Communication, defined as reconciliation enacted through communal ritual practices that reconstruct post-conflict social relations. The concept extends ritual communication and conflict transformation perspectives while highlighting indigenous cultural traditions as sustainable instruments for peacebuilding in multicultural societies.